Rastame Bar Formulation made from Black Rice Flour and Red Bean Flour as An Alternative to Emergency Food - Cahyani Putri, Vina; Estuti, Wiwit (Ann Publisher, 2023)
Geographically and demographically, Indonesia is an area that is prone to natural objects. The National Disaster Management Agency (BNPB) recorded 3,431 natural disasters that have hit various regions in Indonesia from early January to December 2022. Emergency Food Product (EFP) is a product that is designed and used in emergencies without having to go through various cooking processes so that it can be directly consumed. EFP is designed to meet the caloric needs of 233-250 kcal / 50 grams of ingredients. One example of an emergency food product is a snack bar or food bar. This type of research uses the Hedonic Scale Test, which is in the manufacture of Black Rice Flour and Red Bean Flour Rastame Bar products with a Complete Randomized Design (RAL) research design with 3 formulations and 2 repetitions. The organoleptic test was carried out by panelists with a total of 25 moderately trained panelists who were students of the Cirebon Nutrition Study Program level II and III by obtaining the best nutritional content formulation (energy, protein, fat, and carbohydrates) Bar Rastame using the Indonesian Food Composition Table (TKPI) 2017. The treatment used was the ratio of black rice flour to red bean flour respectively by F1 (40%:5%), F2 (35%:10%), and F3 (30%:15%). The selected snack bar is a ratio of 35% black rice flour and 10% red bean flour. The nutritional content of 50 grams of Rastame Bars with a protein content of 5.3 grams, fat content of 4 grams, carbohydrate content of 21.8 grams, and total calories of 143.6 kcal. The characteristics of selected Rastame Bars are a slightly faded blackish color, skimmed milk aroma but not too smelly, hard texture but soft inside, and less sweet taste.